Quantitative analysis of organophosphate pesticides and dialkylphosphates in duplicate diet samples to identify potential sources of measured urinary dialkylphosphates in Japanese women. (1st April 2022) - Tsuchiyama, Tomoyuki; Ito, Yuki; Oya, Naoko; Nomasa, Karin; Sato, Hirotaka; Minato, Kyoko; Kitamori, Kazuya; Oshima, Shiori; Minematsu, Ayako; Niwa, Kazumasa; Katsuhara, Miki; Fukatsu, Kosuke; et al.
Abstract: Increased levels of dialkylphosphates (DAP) in maternal urine are associated with a variety of adverse developmental outcomes in children. Although urinary DAP levels are usually considered to be a marker of exposure to organophosphate (OP) pesticides, excretion of DAP may also increase by ingesting preformed DAP. To date, no study has quantitatively assessed the possible contribution of the dietary intake of preformed DAP and OP pesticides to urinary levels of DAP. Therefore, we aimed to estimate the levels of 6 DAPs and 84 OP pesticides in duplicate diet samples and urine samples collected from 73 women living in urban areas of Japan in 2018. DAP and OP pesticides were detected in 94% and 45% of diet samples, while DAP was detected in 100% of urinary samples, respectively. The average daily intake of preformed DAP was significantly higher than that of parent OP pesticides in our participants. Dimethylphosphate and diethylphosphate were predominant in the preformed DAP, and the estimated average daily intake of total amount of DAP was 78.3 nmol. Fruits and vegetables were the major dietary sources of DAP. Dietary intake of DAP was positively associated with urinary DAP levels, suggesting that a considerable amount of urinary DAP was derived from ingesting preformed DAP. Our results show that attributing urinary DAP levels exclusively to OP pesticide exposure would result in a substantial overestimation of the exposure level. Therefore, the urinary levels of DAP may not be suitable for evaluating OP pesticide exposure in the general urban population. Graphical abstract: Image 1 Highlights: Duplicate diets were collected from Japanese women of reproductive age. Diet samples were analyzed for the presence of OP pesticides and DAPs. The average dietary intake of DAP was much higher than that of OP pesticides. Dietary DAP intake is associated with urine DAP levels.